2021
DOI: 10.1101/2021.01.22.427775
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Insights from Genomes and Genetic Epidemiology of SARS-CoV-2 isolates from the state of Andhra Pradesh

Abstract: Coronavirus disease (COVID-19) emerged from a city in China and has now spread as a global pandemic affecting millions of individuals. The causative agent, SARS-CoV-2 is being extensively studied in terms of its genetic epidemiology using genomic approaches. Andhra Pradesh is one of the major states of India with the third-largest number of COVID-19 cases with limited understanding of its genetic epidemiology. In this study, we have sequenced 293 SARS-CoV-2 genome isolates from Andhra Pradesh with a mean cover… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 16 publications
(16 reference statements)
0
5
0
Order By: Relevance
“…All nine amino acid changes, namely N440K, S477N, V483A, E484K/Q, F490S, S494L/P, N501Y are associated with immune escape 24 , 25 . Viruses with some of these amino acid changes were already known to be circulating in other parts of India 16 , 17 , 24 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…All nine amino acid changes, namely N440K, S477N, V483A, E484K/Q, F490S, S494L/P, N501Y are associated with immune escape 24 , 25 . Viruses with some of these amino acid changes were already known to be circulating in other parts of India 16 , 17 , 24 .…”
Section: Discussionmentioning
confidence: 99%
“…Genomic studies in India have shown that several lineages of SARS-CoV-2 have been introduced, have spread, and fallen below the limit of detection since January 2020 [12][13][14][15][16][17][18][19][20][21][22] . We have previously performed detailed genomic epidemiology of SARS-CoV-2 in the South Indian state of Karnataka, with a population of 64.1 million (Census 2014) 22 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Genomic studies in India have shown that several lineages of SARS-CoV-2 have been introduced, have spread, and fallen below the limit of detection since January 2020 [12][13][14][15][16][17][18][19][20][21][22] . We have previously performed detailed genomic epidemiology of SARS-CoV-2 in the South Indian state of Karnataka, with a population of 64.1 million (Census 2014) 22 .…”
Section: Introductionmentioning
confidence: 99%
“…Multiple lineages of SARS-CoV-2 have been reported from across the world and in India 12,13,[15][16][17][19][20][21][22]27 . There are two ancestral lineages of SARS-CoV-2 in the PANGO classification system, A and B 28 .…”
Section: Introductionmentioning
confidence: 99%